2000
DOI: 10.1080/135048500351537
|View full text |Cite
|
Sign up to set email alerts
|

A yen bloc in Pacific Asia: natural economic symbiosis or overblown rhetorics?

Abstract: Unlike earlier studies, this paper argues that the relevant determinants of East Asian integration ought to be gravity (proximity and size of the regional economics). Using a gravity model of 1975-95 merchandise trade flows, strong evidence was found by East Asian economies integrating and interacting like never before. Interestingly, the most recent evidence also suggests that Japan is in danger of losing its place at the centre of this potentially self-sustaining economic system. In other words, the East Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The analyses in this study utilize cross-sectional data of 50 countries for two years, 1995 and 2000, 1 using gravity models of trade as in Choudhry et al (2000), Subhash and Chua (2000) and Thornton and Goglio (2002). The dependent variable is total bilateral intra-industry trade flow (and its two components) between country i (South Africa) and country j (South Africa's trading partner) at time t (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The analyses in this study utilize cross-sectional data of 50 countries for two years, 1995 and 2000, 1 using gravity models of trade as in Choudhry et al (2000), Subhash and Chua (2000) and Thornton and Goglio (2002). The dependent variable is total bilateral intra-industry trade flow (and its two components) between country i (South Africa) and country j (South Africa's trading partner) at time t (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…On the issue of regionalization centered on Japan, Frankel (1992), using a separate dummy variable speciªcally for bilateral Asian trade with Japan, found little evidence in the regional trade patterns that Japan is transforming itself into a center of trade. In contrast, Choudhry, Abu-Bakar, and Wylie (2000), also using a simple gravity model of trade ºows within East Asian countries (including Hong Kong and Taiwan), concluded that East Asian intraregional trade centered on Japan goes beyond what can be explained by the gravity variables.…”
Section: The Characteristics and Future Of Aseanmentioning
confidence: 98%